Deeper mechanistic insights into epitaxial nickelate electrocatalysts for the oxygen evolution reaction. Issue 31 (15th March 2023) - Kiens, Ellen M.; Choi, Min-Ju; Wei, Luhan; Lu, Qiyang; Wang, Le; Baeumer, Christoph
Abstract : Epitaxial oxide thin films enable electrocatalyst design, e.g. for the oxygen evolution reaction, based on atomic-level structure–property–functionality relationships. Abstract : Mass production of green hydrogen via water electrolysis requires advancements in the performance of electrocatalysts, especially for the oxygen evolution reaction. In this feature article, we highlight how epitaxial nickelates act as model systems to identify atomic-level composition–structure–property–activity relationships, capture dynamic changes under operating conditions, and reveal reaction and failure mechanisms. These insights guide advanced electrocatalyst design with tailored functionality and superior performance. We conclude with an outlook for future developments via operando characterization and multilayer electrocatalyst design.